Reproducibility of endurance performance on a treadmill using a preloaded time trial - Russell, R. D.; Redmann, S. M.; Ravussin, E.; Hunter, G. R.; Larson-Meyer, D. E. (Medicine & Science in Sports & Exercise, 2004)
Purpose: The purpose of this study was to establish a highly reproducible test to measure endurance performance in runners. Methods: We evaluated the reproducibility of endurance performance during a 10-km time trial performed on a treadmill after a 90-min preload run at 65% of maximal oxygen uptake ([latin capital V with dot above]O2max). After screening and a practice test, eight endurance runners (4 men, 4 women, 33.4 +/- 10.1 yr, [latin capital V with dot above]O2max = 60.3 +/- 6.3 mL[middle dot]kg-1[middle dot]min-1 in men and 51.8 +/- 2.2 mL[middle dot]kg-1[middle dot]min-1 in women, mean +/- SD) completed two preloaded time trial tests spaced 3-4 wk apart in men and one menstrual cycle apart in women. A high-carbohydrate diet (15% protein, 10% fat, 75% carbohydrate) was provided the day before both tests. Results: Runners completed time trial 1 and time trial 2 in 45:41 +/- 4:45 and 45:24 +/- 5:03 min:s, respectively (43:29 +/- 5:02 and 43:12 +/- 5:14 min:s for men and 47:53 +/- 3:47 and 47:35 +/- 4:23 min:s for women, trials 1 and 2, respectively). The within-subject coefficient of variation for 10-km time was 1.00% +/- 0.25% (point estimate +/- estimated standard error) (0.54% +/- 0.19% for men and 1.26% +/- 0.45% for women). Conclusion: These results suggest that performance measured as time to complete a 10-km time trial on a treadmill after a 90-min preload is extremely reliable and may be useful for future research assessing the effect of diet, ergogenic substances, or training methods on endurance running performance.